2010
DOI: 10.1038/sj.bjc.6605833
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood-derived miRNA profiles as potential new tools for ovarian cancer screening

Abstract: Background:Screening is an unsolved problem for ovarian cancer (OvCA). As late detection is equivalent to poor prognosis, we analysed whether OvCA patients show diagnostically meaningful microRNA (miRNA) patterns in blood cells.Methods:Blood-borne whole miRNome profiles from 24 patients with OvCA and 15 age- and sex-matched healthy controls were biostatistically evaluated.Results:Student's t-test revealed 147 significantly deregulated miRNAs before and 4 after Benjamini–Hochberg adjustment. Although these incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
135
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 47 publications
4
135
0
2
Order By: Relevance
“…Given the role of the miR-506-514 cluster in melanocyte transformation, it may be an early event critical for the shift from benign nevi to an early melanoma and therefore could be a critical biomarker with the potential to enable earlier diagnosis and inform treatment decisions. Tumor-associated miRNA patterns have been shown to be highly tissue specific (Ha¨usler et al, 2010) and very stable in tissue, blood and in formalin-fixed, paraffin-embedded tissue, hence information about altered miRNA levels could be obtained from multiple sources and quantified by standard methods at any time during the course of the disease (Segura et al, 2010). A proof-of-principle study was recently conducted to examine whole-blood miRNA profiles for identifying ovarian cancer or monitoring its relapse (Osawa and Fisher, 2008;Leidinger et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role of the miR-506-514 cluster in melanocyte transformation, it may be an early event critical for the shift from benign nevi to an early melanoma and therefore could be a critical biomarker with the potential to enable earlier diagnosis and inform treatment decisions. Tumor-associated miRNA patterns have been shown to be highly tissue specific (Ha¨usler et al, 2010) and very stable in tissue, blood and in formalin-fixed, paraffin-embedded tissue, hence information about altered miRNA levels could be obtained from multiple sources and quantified by standard methods at any time during the course of the disease (Segura et al, 2010). A proof-of-principle study was recently conducted to examine whole-blood miRNA profiles for identifying ovarian cancer or monitoring its relapse (Osawa and Fisher, 2008;Leidinger et al, 2010).…”
mentioning
confidence: 99%
“…A proof-of-principle study was recently conducted to examine whole-blood miRNA profiles for identifying ovarian cancer or monitoring its relapse (Osawa and Fisher, 2008;Leidinger et al, 2010). Although the study was small, the preliminary positive results in identifying a subset of miRNAs consistently and specifically altered in individuals with ovarian cancer supports the future clinical utility of altered miRNA signatures (Ha¨usler et al, 2010). With the existing limitations in the current melanoma staging system, as well as the inability to identify early neoplastic cells or differentiate melanomas that are likely to metastasize, it is clear that the addition of a molecular marker predictive of these features would provide profound clinical benefit to melanoma patients.…”
mentioning
confidence: 99%
“…Exosomes and EVs play a crucial role in intercellular communication, including promotion of sperm maturation, regulation of immune function, release of miRNA for a wide array of regulatory functions, as well as other roles currently being studied (Raposo and Stoorvogel, 2013). Serum and whole blood have proved an acceptable source of EV-derived miRNA profiles, thus providing a potential blood-borne biomarker candidate for various disease and physiological states (Häusler et al, 2010;Reid et al, 2011). Human based disease research has revealed significant differences in miRNA abundance for many cancers (Lawrie et al, 2008;Häusler et al, 2010), heart disease (Tijsen et al, 2010) and sepsis (Wang et al, 2010).…”
Section: Mirnas: Potential Biomarkers For Pregnancy Diagnosismentioning
confidence: 99%
“…Serum and whole blood have proved an acceptable source of EV-derived miRNA profiles, thus providing a potential blood-borne biomarker candidate for various disease and physiological states (Häusler et al, 2010;Reid et al, 2011). Human based disease research has revealed significant differences in miRNA abundance for many cancers (Lawrie et al, 2008;Häusler et al, 2010), heart disease (Tijsen et al, 2010) and sepsis (Wang et al, 2010). In addition, circulating miRNAs in maternal serum have been observed as potential biomarkers of pregnancy status due to their significant impact on gene expression and regulation (Chim et al, 2008).…”
Section: Mirnas: Potential Biomarkers For Pregnancy Diagnosismentioning
confidence: 99%
“…Interestingly, Valeri and colleagues (2010) reported that a noncoding miRNA designated as miR-155 is significantly overexpressed in human colorectal cancers and that an inverse correlation exists between the expression of miR-155 and the expression of hMLH1 or hMSH2 proteins in these tissues. miR-155 has been detected in blood samples derived from patients with ovarian cancer, though the sensitivity is still too low to be used as a reliable and predictive indicator of disease progression (Hausler et al, 2010). miR-155 has been put forth as a potential biomarker for the detection of early pancreatic neoplasia (Habbe et al, 2009).…”
Section: Human Muts Homolog 2 (Hmsh2) and Human Mutl Homolog 1 (Hmlh1)mentioning
confidence: 99%